Vision of irrigation - Fernando Braz-Tangerino; Maria Isabel Ferreira; Miguel Angel Moreno-Hidalgo; Enrique Playán; Inmaculada Pulido-Calvo; Leonor Rodríguez-Sinobas; José María Tarjuelo; Ricardo Serralheiro (Ingeniería del Agua)
Irrigation not only has been a key factor for the development and maintenance of human societies but it still plays this role now and it is foreseen that in the future as well. Its evolution has been constrained to the advance in knowledge on matters regarding Agronomy and Water Engineering and in technology however, many challenges deserve further research. It is worth to note that Brazil has strongly promoted irrigation in the last decade. Within the limited extension of this article, some current topics in irrigation, some of them are innovative such us the research line studying water flow in soil-plant in Mediterranean plants and its consequences on water use,. and future challenges are presented with the purpose of stimulate publication of Irrigation papers in the journal “Ingeniería del Agua” among Portuguese and Spanish language communities.